Search for Roots in Manju Kapur’s a Married Woman - N. Jhansi; A.Subramanian (International Journal of Psychosocial Rehabilitation, 2020)
Women have always been ignored and she longs for appreciation and recognition in life. The moral values and age old traditions are always there in the minds of every individual. The Westernization impact on Indian Society and its reflection in the characters of educated Indian women is inevitable. Manju Kapur’s A Married Woman is no exception to that. Manju Kapoor’s novels portrays the Indian women characters who are in continuous search for roots and identity. Kapur is known for her bold themes in her novels like lesbianism, divorce, infertility, adoption, etc. This paper focuses on the struggle between family traditions and customs that run in the minds of the protagonist in “A Married Woman” which makes her to feel dissatisfaction and drives her to run-in search of roots, identity crisis and their minds are filled with the sense of nowhere belongingness.